Performance Evaluation Using the DEA-Stepwise Modeling Approach Method: Case Study of the Export-Import Sector in Indonesia - Erni Puspanantasari Putri (Jurnal Serambi Engineering, 2024)
The export and import industry are now a significant determinant of a nation's economic progress in the age of globalization. A nation's ability to export helps it earn foreign cash that it can utilize to fund development and spur economic expansion. Conversely, import-related activities might assist in satisfying the need for products or services that cannot be effectively provided domestically. Entrepreneurs can increase the competitiveness of local products and the quality of their products through imports and exports, which will enhance both industrial progress and community welfare. To maximize the nation's economic progress, the government and business owners must continue to boost import-export activity. The objective of this study is to evaluate Indonesia's export-import sector's performance using the stepwise modeling approach and the DEA method. One technique to determine which export-import sector activities are effective and ineffective is performance evaluation. These two sectors can support the country's economy in this way and do so with a long-term approach. The research results indicate that efficient DMUs have the smallest presentation (20%) and inefficient DMUs have the largest percentage (80%). The efficient DMU category is C (1). Inefficient DMU categories, namely: SK (0.285), S (0.193), M-US (0.472), and T-J (0.11).